Assimilation of white-collar offenses in paraguayan Penal Code : Summary of punitive and preventive approach (Legal journal - Research in Legal and Social Sciences, 2020)
The progress of society brings along the proliferation of enterprises dedicated to different areas in economic activities, this also forces the State to adjust to theeconomic progress and to establish institutions with specialized officials that can deal with this type of enterprises. This, in turn, creates the need to count withemployees who can have access to information and assets of the enterprises they manage or work for. That same need applies to public entities. The illegal businesses related to this type of activities gave rise to a new labelling of economic crime, namely the white-collar offenses, whose main characteristic is the active subject, that must count with a certain socioeconomic status for the comission of an illicit act. In this context and in order to tackle these offenses, Paraguay has implemented actions such as the establishment of Specialized Units, the enactment of specific legal norms that help the prosecution and enhancement of the criminal investigations related to these offenses.
Keywords: white-collar offenses; economic crime; punishable act; economic criminal law